Об ареально-типологическом изучении балтизмов в белорусских говорах - Станкевич, А. (Baltistica, 1988)
ON THE AREA-TYPOLOGICAL STUDY OF THE BALTIC ORIGIN WORDS IN BYELORUSSIAN DIALECTS The paper deals with the area-typological characteristics of the words of Baltic origin, functioning in Byelorussian dialects. It concerns the zones of functioning of the words of Baltic origin on the linguistic map of Byelorussia, taking into account the degree of their concentration (strong, intermediate, weak). Considering the role of the words of Baltic origin in the lexical system of Byelorussian dialects, the main types are distinguished, namely: (1) the words of Baltic origin comprising all the dialect areas of Byelorussia; (2) the words of Baltic origin used in some group of dialects generally in the neighbouring areas; (3) the words of Baltic origin concentrated in the dialects of the north-western part of Byelorussia. Besides, the paper describes the types of areas characteristic of the Baltic origin words in Byelorussian dialects.